PRAGMATIC FUNCTIONS OF MYTH-BASED PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK DISCOURSES (International journal of artificial intelligence, 2026)
The article explores the pragmatic functions of myth-based phraseologisms in English and Uzbek discourses from a comparative perspective. The exploration aims to identify and analyze the expressive, evaluative, sensitive, and persuasive functions performed by phraseological units involving mythological elements in actual discourse. The research employs comparative, semantic-pragmatic, and contextual analysis approaches. The results reveal that mythological units in both languages play significant role in developing expressiveness and transferring cultural meanings in communication. While some pragmatic functions illustrate general characteristics, others are deeply rooted in national and cultural specificity. English myth-based phraseologisms are mainly affected by Greco-Roman mythology, whereas Uzbek unit express folklore traditions and Eastern contribute to the field of comparative linguistics, phraseology, and linguistic pragmatics by maintaining both shared and language-specific pragmatic traits of mythological phraseological units.